2002
DOI: 10.1038/sj.leu.2402468
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, cytogenetics and outcome in acute lymphoblastic and myeloid leukaemia of infancy: report from the MRC Childhood Leukaemia working party

Abstract: The clinical features, cytogenetics and response to treatment have been examined in 180 infants (aged Ͻ1 year) with acute leukaemia; 118 with acute lymphoblastic leukaemia (ALL) and 62 with acute myeloid leukaemia (AML). Comparison of clinical features showed no difference in age or sex distribution between infants with ALL and AML but infants with ALL tended to have higher leucocyte counts at presentation. Cytogenetic abnormalities involving 11q23 were found in 66% of ALL and 35% of AML cases, the commonest, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
1
13

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 31 publications
4
72
1
13
Order By: Relevance
“…[7][8] However, the t(9;11) translocation, although the most common 11q23 chromosomal abnormality associated with de novo AML with monocytic differentiation (FAB M4 and M5) and DNA-topoisomerase inhibitor therapyrelated AML, is only rarely seen in precursor B-ALL. [10][11][12]26,27 Although the exact fusion gene in our cases was not determined, studies of the t(9;11) translocation in AML most commonly results in a fusion of the MLL and AF9 genes. 26 Additional studies have suggested that the resultant MLL/AF9 fusion gene is involved in myeloproliferation 13 and leukemogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8] However, the t(9;11) translocation, although the most common 11q23 chromosomal abnormality associated with de novo AML with monocytic differentiation (FAB M4 and M5) and DNA-topoisomerase inhibitor therapyrelated AML, is only rarely seen in precursor B-ALL. [10][11][12]26,27 Although the exact fusion gene in our cases was not determined, studies of the t(9;11) translocation in AML most commonly results in a fusion of the MLL and AF9 genes. 26 Additional studies have suggested that the resultant MLL/AF9 fusion gene is involved in myeloproliferation 13 and leukemogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Infantile B-ALL, generally a precursor B-ALL, has a poor prognosis and is frequently associated with rearrangement of the MLL gene [10][11][12] through different genetic aberrations involving chromosome 11q23. Reciprocal translocations are most common and the following are most common in decreasing order of frequency: t(4;11)(q21;q23), t(11;19)(q23;p13.3) and t(9;11)(p21-22;q23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Thus, it is conceivable that the type of hematopoietic cells targeted by MLL rearrangements influences the drug sensitivity of transformed blasts. According to recent evidence on childhood ALL with 11q23 alterations, 7,8 it is possible that leukemic cells with MLL rearrangement involve early progenitor cells that are more likely to exhibit drug resistance than are cells from patients older than 1 year or, in case of AML with FAB M5, harboring the same genetic change.…”
Section: To the Editormentioning
confidence: 99%
“…The clinical and biological features of infant leukemia are different from those of childhood leukemia. Infants with this disease more frequently have hyperleukocytosis, massive hepatosplenomegaly, and central nervous system (CNS) involvement [2][3][4]. Infant ALL usually presents with CD10-negative precursor-B immunophenotype, and the blast cells often express myeloid-associated antigens [2,3,5].…”
Section: Introductionmentioning
confidence: 99%